"There Is Something Very Personal About Seeing Someone's Face": Provider Perceptions of Video Visits in Home-Based Primary Care During COVID-19. (November 2021) - Franzosa, Emily; Gorbenko, Ksenia; Brody, Abraham A.; Leff, Bruce; Ritchie, Christine S.; Kinosian, Bruce; Sheehan, Orla C.; Federman, Alex D.; Ornstein, Katherine A.
The rapid deployment of video visits during COVID-19 may have posed unique challenges for home-based primary care (HBPC) practices due to their hands-on model of care and older adult population. This qualitative study examined provider perceptions of video visits during the first wave of the COVID-19 crisis in New York City (NYC) through interviews with HBPC clinical/medical directors, program managers, nurse practitioners/nurse managers, and social work managers ( n = 13) at six NYC-area practices. Providers reported a combination of commercial (health system-supported) and consumer (e.g., FaceTime) technological platforms was essential. Video visit benefits included triaging patient needs, collecting patient information, and increasing scheduling capacity. Barriers included cognitive and sensory abilities, technology access, reliance on caregivers and aides, addressing sensitive topics, and incomplete exams. Effectively integrating video visits requires considering how technology can be proactively integrated into practice. A policy that promotes platform flexibility will be crucial in fostering video integration.